Analisis Variasi Temperatur Artificial aging Terhadap Struktur Mikro dan Sifat Mekanik Pada Aluminium 6061 T6 - Widyawati, Fauzi; Solahudin, Muhammad Miftah; Hidayat, Syamsul (SPECTA Journal of Technology, 2024)
Aluminum alloy 6061 series has been used extensively in the manufacturing industry. This aluminum material was chosen because it has many advantages. The level of superiority of aluminum can be seen in terms of good machining ability, perfect surface finish, good level of corrosion resistance, and high strength. In this research, the samples used 6061 series aluminum alloy, and an artificial aging process was carried out with temperature variations of 150ᴼC, 175ᴼC, 200ᴼC, and a holding time of 8 hours. Following this, measurements were performed for hardness, impact, and microstructural observations. The research shows that the mechanical properties of the alloy after the artificial aging process tend to decrease as temperature variations increase, for the hardness value obtained at 150ᴼC is 57.34 HRB, 175ᴼC is 55.42 HRB, 200ᴼC is 46.12 HRB. For the impact value, the optimal value was obtained at a temperature of 150ᴼC with a value of 41.4 J/mm2. When the microstructure was examined, it was discovered that each specimen's AlMg2Si compound was the consequence of the artificial aging process.